Offline segmentation and script recognition of Hindi using knowledge based approach and multi layered perceptron neural network. Issue 4 (4th July 2017) - Sharma, Neha V; Kavita,; Aggarwal, Gaurav
Abstract: The following paper focusses on a segmentation technique for most widely used language in India i.e. Hindi. Because of variations in writing styles and intricate structures, this field is drawing a lot of attention from researchers. This paper proposes a system which mines and identifies offline Hindi words using MLP Neural Network. Here we are using three layer architecture of neural networks that consists of a layer for Input, Hidden layer and a Resultant layer. Also segmentation is done using Knowledge Based Approach. The success rate after segmentation is 94.87%. Also the overall recognition accuracy is 85.78%.